Chemical properties and antioxidant activity of sweetened red ginger extract fermented with kombucha culture - Setyani Budiari; Hani Mulyani; Yati Maryati; Euis Filailla; Anastasia Fitria Devi; Hakiki Melanie (AGROINTEK, 2023)
Kombucha is a renowned fermented drink for its diverse health benefits. This research aims to evaluate sweetened red ginger extract as an alternative substrate in making kombucha by observing the chemical properties (pH, total acid, total sugar, total polyphenol, chemical compound profile using LC-MS/MS) and the antioxidant activity. Three variables were varied, i.e., red ginger concentration (1, 5, and 10%), kombucha culture concentration (10 and 20%), and fermentation time (0, 6, and 12 days). The total sugar and pH declined during fermentation while the titratable acidity, polyphenol, and antioxidant activity increased. The kombucha prepared with 20% culture concentration resulted in a greater reduction of pH and increase of titratable acidity, total polyphenol, and antioxidant activity than the one prepared with 10% culture concentration. The red ginger kombucha prepared with 10% ginger and 20% culture in 12 days displayed the highest antioxidant activity. It revealed ten active compounds under the LC-MS/MS investigation, i.e., 3’,4’,5’,5,7,8-hexame-thoxy flavone, 6-gingerol, evodin, isosakuranetin-7-rutinoside, methyl ophiopogonanone A, narirutin, neohesperidin, ononin, sinensetin, and shogaol. This research shows that red ginger extract fermentation using kombucha culture can be an alternative technology to produce red ginger-based functional drinks with healthy organic acids, healthy polyphenols, and antioxidant activity.